The Application of Interpretive Structural Modeling Technique (ISM) to Study Adopting model of Green Supply Chain Management - Wongthongchai, Jirawat; Saenchaiyathon, Krittapha (International Journal of Engineering and Technology, 2019)
Environmental concern has increasingly become an important issue in supply chain management. Firms would gain competitive advantage by adopting green supply chain management. However, green supply chain management will work effectively and efficiently if the firmâ€™s human resource department plays a major role in creating the awareness and the value of adopting the concept of green. Hence, the objective of this study was to investigate the relationships among all the relevant elements/variables concerning green supply chain management and the role of human resource department in the organization. We adopted the ISM technique to examine the relationships among those elements/variables derived from the literature review, group discussion, and in-depth interviews. Additionally, group discussion and in-depth interviews were also adopted to examine the relationships among those elements/variables. The results were satisfactory and the relationships among those key elements/variables were established. Thus, the ISM technique is very useful in research and the relationships derived in this study are considered robust.Â